ROLE OF DIGITAL MEDIA IN PROMOTING SUSTAINABLE MENSTRUAL PRODUCT AMONG STEM AND NON-STEM STUDENTS OF BBAU: AN EMPIRICAL STUDY - Dubey, Shweta; Padhy, Mahendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction: Sustainable menstrual products (SMPs), including menstrual cups and organic pads, provide safer and eco-friendly alternatives to conventional products that contribute to health risks and environmental damage. In India, 336 million menstruators endure health perils, and the Earth pays the price with an estimated 12.3 billion tonnes of non-biodegradable sanitary waste generated annually (citation required). Despite increasing awareness, adoption of SMPs remains low due to cultural stigma, affordability issues, and lack of access. This study investigates the role of digital media in promoting awareness and adoption of SMPs among female students at Babasaheb Bhimrao Ambedkar University (BBAU), with a comparative focus on STEM and non-STEM groups. Methods: A quantitative comparative design was applied with a stratified random sample of 100 students (50 STEM, 50 non-STEM). Structured surveys measured awareness, adoption, digital literacy, and exposure to social media campaigns. Data were analyzed using t-tests, chi-square, correlation, regression, ANOVA, and factor analysis. Results: STEM students showed higher awareness (M=8.1 vs. 6.3, p<0.001) and adoption rates (45% vs. 32%, p<0.005). Digital literacy was strongly correlated with awareness (r=0.65, p=0.001), and regression identified social media use, digital literacy, and educational background as significant predictors. Discussion and Conclusion: Digital media has strong potential to democratize menstrual health discourse, but bridging the awareness–adoption gap requires culturally sensitive campaigns, affordability considerations, and improved access to sustainable alternatives.